The Role of the Self-Presence for Interactive Large Digital Displays: Gesture Interactivity and Mirrored-Self Image for Advertising Content. Issue 16 (2nd October 2022) - Jung, Soyoung; Lee, Daeun; You, Soyon; Biocca, Frank; Kum-Biocca, Hannah
ABSTRACT: The gesture interactivity and self-mirroring effects of large digital displays, also known as digital signage, was investigated using the self-presence theory and engagement. By extending the interactive effects of gesture and self-mirroring from the immersive environment to a large interactive display (LID), this study found the implicit mediating roles of social presence and engagement for advertising effectiveness through a 2 (gesture; non-gesture vs. gesture interactivity) x 2 (self-representation; non-self-mirroring vs. self-mirroring interactivity) between-subject design (N = 81) experiment. The results indicated that gesture interactivity enhances a feeling of self-presence, not self-mirroring, and it positively fosters psychological engagement with advertising content. In turn, the heightened engagement results in better advertising effectiveness, such as brand attitude, purchase intention, and recall.